Spontaneous pneumomediastinum due to paralytic rabies - Wang,Wuping (2013)
Rabies is a fatal disease resulting from rabies virus infection, causing severe neurological symptoms and ultimately death by destroying the nervous system. In general, a patient tends to see a neurologist or an infectious diseases physician, with very common and typical discipline-related signs and symptoms, such as hydrophobia, aerophobia, and mental disorders. However, we reported a rabies patient who was first admitted to see a thoracic surgeon with spontaneous pneumomediastinum.